Endoscopic improvement of mucosal lesions in patients with moderate to severe ileocolonic Crohn's disease following treatment with certolizumab pegol. Issue 2 (23rd April 2012) - Hébuterne, Xavier; Lémann, Marc; Bouhnik, Yoram; Dewit, Olivier; Dupas, Jean-Louis; Mross, Michael; D'Haens, Geert; Mitchev, Krassimir; Ernault, Étienne; Vermeire, Séverine; Brixi-Benmansour, Hedia; Moreels, Tom G; et al.
Abstract : Objective: To evaluate the efficacy of certolizumab pegol (CZP) in improving endoscopic lesions in patients with active ileocolonic Crohn's disease (CD). Methods: This phase IIIB multicentre open-label clinical trial enrolled 89 adult patients with active endoscopic disease (ulceration in ≥2 intestinal segments with a Crohn's Disease Endoscopic Index of Severity (CDEIS) score ≥8 points). Patients received subcutaneous CZP 400 mg at weeks 0, 2 and 4 and every 4 weeks up to week 52. Endoscopic evaluations were performed at weeks 0, 10 and 54. The primary outcome was mean change in CDEIS score at week 10; secondary outcome measures included endoscopic response (decrease in CDEIS score >5 points), remission (CDEIS score <6), complete remission (CDEIS score <3) and mucosal healing (no ulcer) at weeks 10 and 54. Results: In the intention-to-treat population (n=89) the mean±SD CDEIS score was 14.5±5.3 at baseline; the mean decrease in CDEIS score at week 10 was 5.7 (95% CI 4.6 to 6.8, p<0.0001). Rates of endoscopic response, endoscopic remission, complete endoscopic remission and mucosal healing at week 10 were 54%, 37%, 10% and 4%, respectively. At week 54 the corresponding rates were 49%, 27%, 14% and 8%, respectively. The safety profile was consistent with that of previous CZP trials. Conclusions: Following CZP treatment in patients with active CD, endoscopic lesions were improved as shown by the decrease in mean CDEIS score and by endoscopic response and remission rates. These benefits were achieved as early as week 10 and were generally maintained through week 54. Clinical Trial Registration Number: NCT00297648.